FAKTOR PENYEBAB ANAK MELAKUKAN TINDAKAN KRIMINAL (Studi Kasus Lembaga Pemasyarakatan Pekanbaru Kelas II B) - Khairul Ihsan; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The involvement of children in crime who are in public life is awkward in society. There are many factors that could be behind someone committed a crime, such as: opposition and competition culture, differences in political ideology, density and composition of the population, differences in the distribution of cultural differences in wealth and income, the mentality unstable, as well as factors such basic biological factors, psychological and socioemotional. Many negative impact given by the development, progress and demands on Children, there spotlight very attention that struck the Indonesian Nations Children's happened in the city of Pekanbaru in Riau, one of which criminality committed by the Son. Number of Children criminality committed every turn of the year still amounts.The data were analyzed descriptively ie by making a description or a description of several phenomena found in the field. After all the primary data can be collected from the respondents, were analyzed qualitatively. That the causes of the Children's Criminal particularly in the city of Pekanbaru is due to economic, educational, environmental, law enforcement and is also inseparable from the negligence of parents in educating children.Keywords: Criminal Kids, Prisonof Class II B, Factor Of Criminals